Morquio's Disease - Hariarti S. Pramuljo; L. A. Tamaela; W.T. Karyomanggow (Paediatrica Indonesiana, 1980)
Morquio's disease belongs to the group of mucopolysaccharidosis which causes deformities of the bones. The diagnosis is made by radiological examinations and others such as biochemical examination. Four cases of Morquio's disease are presented, which are the first reported in the Indonesian literature. All cases are of Chinese origin. Cervical fusion had been done in one of the cases to prevent the complication of neurologic sequelae and sudden death. The symptoms, diagnosis and therapeutic measures to prevent sequelae have been discussed.